Cp*Co(III)‐Catalyzed Coupling of Benzamides with α, β‐Unsaturated Carbonyl Compounds: Preparation of Aliphatic Ketones and Azepinones. Issue 14 (12th February 2018) - Chirila, Paula G.; Adams, Joshua; Dirjal, Amir; Hamilton, Alex; Whiteoak, Christopher J.
Abstract: A Cp*Co III ‐catalyzed C−H functionalization of benzamide substrates with α, β‐unsaturated ketones has been optimized, providing a facile route towards aliphatic ketone products. When employing α, β‐unsaturated aldehydes as coupling partners, under the optimized protocol, a cascade reaction forming azepinones has also been developed. Finally, DFT studies have demonstrated how stabilization of a metallo‐enol intermediate when employing α, β‐unsaturated ketones is the driving force leading to the observed aliphatic ketone product rather than olefinic products reported using α, β‐unsaturated esters as coupling partners. Abstract : On the way to seventh heaven : A Cp*Co III ‐catalyzed C−H functionalization of benzamides with methyl α, β‐unsaturated ketone, providing aliphatic ketone products is described. When acrolein is employed, 7‐membered azepinones are generated through a cascade reaction. Finally, DFT studies have provided a clear explanation of the mechanism for the initial C−H functionalization protocol, clearly explaining the product outcome.